Effect of selected footwork drills on motor fitness variables of badminton players - Nirendan, J.; Murugavel, K. (Bharathiar National Journal of Physical Education and Exercise Science, 2019)
This study aimed to find out the effect of selected footwork drills on motor fitness components of school level badminton players. To achieve the purpose of the study thirty school level badminton players were selected from various badminton clubs at Coimbatore. Their age ranged between 12-16 years. They were divided into two equal groups consists of fifteen each. No attempt was made to equate the groups. Experimental Group was given Footwork drills (FWD) for the period of 8 weeks and Group II acted as control group (CG), the subjects in control group was not engage in any training programme other than their regular activity. The motor fitness components, agility was assessed by 4x10mts shuttle run test and Reaction Time was assessed by Penney Cup Test The data collected from the subjects was statistically analyzed with `t` ratio to find out significant improvement if any at 0.05 level of confidence. The result of the agility and reaction time improved significantly due to effect of selected footwork drills with the limitations of (diet, climate, life style ) status and previous training the result of the present study coincide findings of the investigation done by different experts in the field of sports sciences. Footwork drills significantly improved agility and reaction time of school level badmintonplayers.